2020
DOI: 10.1523/eneuro.0212-19.2019
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison between Mouse,In Silico, and Robot Odor Plume Navigation Reveals Advantages of Mouse Odor Tracking

Abstract: Localization of odors is essential to animal survival, and thus animals are adept at odor navigation. In natural conditions animals encounter odor sources in which odor is carried by air flow varying in complexity. We sought to identify potential minimalist strategies that can effectively be used for odor-based navigation and asses their performance in an increasingly chaotic environment. To do so, we compared mouse, in silico model, and Arduino-based robot odor-localization behavior in a standardized odor lan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 55 publications
0
23
0
Order By: Relevance
“…A growing body of literature has focused on understanding the behavioral strategies for odor-source localization in freely moving mammals (Findley et al, 2020;Gire et al, 2016;Gumaste et al, 2020;Liu et al, 2020). However, correlating real-time olfactory information with behavior and physiological recordings from freely moving animals has been a challenging avenue due to the dynamic nature of the olfactory stimulus.…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of literature has focused on understanding the behavioral strategies for odor-source localization in freely moving mammals (Findley et al, 2020;Gire et al, 2016;Gumaste et al, 2020;Liu et al, 2020). However, correlating real-time olfactory information with behavior and physiological recordings from freely moving animals has been a challenging avenue due to the dynamic nature of the olfactory stimulus.…”
Section: Discussionmentioning
confidence: 99%
“…Although inter-sniff comparisons in mice show that MT cells can detect the sign and magnitude of changes in odor concentration (Parabucki et al, 2019), it is unknown whether they are able to resolve the dynamics of natural plumes, which span across a range of temporal scales. If odor concentration dynamics are resolved, computational work has shown that they are informative for olfactory search ( (Baker et al, 2018); (Gumaste et al, 2020)). To avoid the complexity of stochastic odor plumes, the averaging of odor concentration dynamics could be an alternative strategy to navigate olfactory environments.…”
Section: Discussionmentioning
confidence: 99%
“…Mean odor concentration levels are moderated both by the distance from an odor source and how close an animal is to the central stream of the plume (Crimaldi and Koseff, 2001). While this measure is potentially informative, it does not by itself sufficiently inform decision-making on the timescale observed in rodents (Gumaste et al, 2020). Therefore, it is likely that the mouse relies upon spatiotemporal features of the plume for olfactory search as information can be extracted from odor concentration dynamics (Baker et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The animal is rewarded after successfully navigating towards the port releasing odour. Bottom right: Time averaged and normalised PID recordings of odour from port 1 and 2 across the flow chamber (from Gumaste et al 2020). c Top: Schematic of two-dimensional odour plume tracking behaviour.…”
Section: Odour Trail Trackingmentioning
confidence: 99%